Oxygen Evolution Electrocatalysis of a Single MOF-derived Composite Nanoparticle on the tip of a Nanoelectrode - Aiyappa, Harshitha Barike; Wilde, Patrick; QuasT, Thomas; Masa, Justus; Andronescu, Corina; Schuhmann, Wolfgang (Angewandte Chemie International Edition, 2019)
Determination of the intrinsic electrocatalytic activity of nanomaterials by means of macroelectrode techniques is compromised by ensemble and film effects. Here, a unique “particle on a stick” approach is used to grow a single metal–organic framework (MOF; ZIF-67) nanoparticle on a nanoelectrode surface which is pyrolyzed to generate a cobalt/nitrogen-doped carbon (CoN/C) composite nanoparticle that exhibits very high catalytic activity towards the oxygen evolution reaction (OER) with a current density of up to 230 mA cm−2 at 1.77 V (vs. RHE), and a high turnover frequency (TOF) of 29.7 s−1 at 540 mV overpotential. Identical location transmission electron microscopy (IL-TEM) analysis substantiates the “self-sacrificial” template nature of the MOF, while post-electrocatalysis studies reveal agglomeration of Co centers within the CoN/C composite during the OER. “Single-entity” electrochemical analysis allows for deriving the intrinsic electrocatalytic activity and furnishes insight into the transient behavior of the electrocatalyst under reaction conditions.